GAYA HIDUP REMAJA PERKOTAAN DAN TANTANGANNYA TERHADAP PENGUATAN IDENTITAS NASIONAL - Palti Hansd T. M. Simanjuntak; Santa Nananda Sebayang; Elina Rosa Sihotang; Amos Frans Abdial Tarigan; Thamrin Daulat Dorianus Simanjuntak; Adika Indotua Nainggolan; Prini Desima Evawani Ambarita (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The transformation of urban society and the widespread use of digital technology have deeply influenced the lifestyles of adolescents. Many urban youths are increasingly adopting modern, instant, and globally popular habits that often conflict with national cultural values. This tendency leads to a weakening of national identity, as reflected in the loss of emotional ties to local culture, limited knowledge of national history, and reduced pride in being Indonesian. This study aims to examine the characteristics of urban adolescent lifestyles, identify the challenges they pose to the development of national identity, and propose relevant strategies to strengthen civic awareness. Using a qualitative descriptive method, the research highlights several contributing factors, including cultural dominance from abroad, the lack of contextual civic education, weak parental guidance, and limited exposure to positive local role models. The findings suggest that strengthening national identity requires a holistic approach: revitalizing value-based education, promoting cultural literacy, involving families, encouraging digital ethics, and collaborating with nationalist public figures. With integrated efforts, urban youth can grow as global citizens who remain proud of and loyal to their cultural roots as Indonesians.